Neuroinflammation in the biochemical mechanisms of amyloidosis - Sokolik, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
The review presents an analysis of the current level of understanding of the influence of the neuroinflammatory process on the biochemical mechanisms of the onset, acceleration and course of amyloidosis in neurodegenerative pathology. Particular attention is paid to the function of the cytokine link of the innate immunity of the brain’s nervous tissue. In particular, the influence of proinflammatory cytokines of the first wave of the cytokine cascade on the processes of memory and regulation of neuroplasticity is analyzed in detail. Specificity of the response of innate immunity in the signaling pathways of interleukin-1β and tumor necrosis factor α effects in terms of excess synthesis and amyloidogenic processing of the β-amyloid peptide precursor is noted. The character of the influence of cytokines on cells (autocrine, paracrine or systemic) is considered and the scheme of the cascade of cytokine activation at amyloidosis is presented. The review also focuses on other regulatory peptides: interleukin-6, interleukin-10, protein S100B, and the like. Namely, the features of signal transduction in the interaction of interleukin-6 with their membrane or soluble receptors are presented, and the latter’s need for stimulation of neurite outgrowth and survival of neurons, as well as regeneration of the nerves through remyelinisation. Information is given on post-transcriptional regulation of anti-inflammatory interleukin-10 level, which contains the control of the stability of mRNA with the help of AC-enriched elements and individual miRNAs and indicates its function in suppressing the synthesis of proinflammatory cytokines. Underlined the ability of S100B to enhance the expression of the precursor of the β-amyloid peptide and its mRNA, leading to learning disorder and memory and brain atrophy. Detailed information is presented on the effect of each of the cytokines examined on the synthesis and metabolism of the protein of the precursor of the β-amyloid peptide, as well as own results on the induction of proinflammatory cytokines in mononuclear cells in vitro and in the neocortex and hippocampus of the brain of experimental animals in vivo under the influence of β-amyloid peptides aggregates. It is generalized that cytokines primarily activate the synthesis of the protein of the precursor of the β-amyloid peptide and the formation of β-amyloid peptide aggregates during chronic exposure, as observed at aging or Alzheimer’s disease, therefore, they can directly participate in the amplification of amyloidogenesis.